Similar localization of conformational IgE epitopes on the house dust mite allergens Der p 5 and Der p 21 despite limited IgE cross‐reactivity. Issue 8 (21st February 2018) - Curin, M.; Garmatiuk, T.; Resch‐Marat, Y.; Chen, K. W.; Hofer, G.; Fauland, K.; Keller, W.; Hemmer, W.; Vrtala, S.; Focke‐Tejkl, M.; Valenta, R.
Abstract: Background: Due to high IgE recognition frequency and high allergenic activity, Der p 5 and Der p 21 are clinically important house dust mite (HDM) allergens. The objective of this study was to characterize the immunodominant IgE epitopes of Der p 5 and Der p 21 responsible for their high allergenic activity. Methods: A panel of 12 overlapping peptides spanning the Der p 5 and Der p 21 sequence were synthesized to search for sequential IgE epitopes by direct testing for allergic patients' IgE reactivity. Peptide‐specific antibodies raised in rabbits were used in inhibition studies for localizing conformational IgE epitopes which were visualized on the surfaces of the allergen structures by molecular modelling. IgE cross‐reactivity between the allergens was investigated by IgE inhibition studies. Results: Immunodominant IgE epitopes defined by allergic patients' IgE on Der p 5 and Der p 21 were primarily of the conformational, discontinuous type including N‐ and C‐terminal portions of the protein. They could be located on each allergen on one area with similar localization, but despite similar structure of the allergens, no relevant IgE cross‐reactivity could be detected. Conclusion: Our study shows that Der p 5 and Der p 21 contain a major conformational IgE epitope‐containing area located on similar portions of their structure, but they lack relevant IgE cross‐reactivity. These data are important for the development of modern allergy vaccines based on defined molecules for allergen‐specific immunotherapy of HDM allergy.